Purification and characterization of malate dehydrogenase from sheep liver (Ovis aries): Application in AST assay diagnostic kit - Doaa A. Darwish, Hassan M.M. Masoud, Mohamed M. Abdel-Monsef, Mohamed S. Helmy, Mahmoud A. Ibrahim (Journal of Applied Pharmaceutical Science, 2018)
Malate dehydrogenase enzyme is a major component in aspartate aminotransferase (AST) diagnostic kit that used in diagnosis and monitoring of liver diseases. This study aimed at purification and characterization of MDH enzyme from sheep liver for direct application in preparation of AST kit. Two malate dehydrogenase isoenzymes were resolved from sheep liver by chromatography on DEAE-cellulose column, one major sheep liver MDH (SLMDH) and another minor one. SLMDH was extracted and purified by ammonium sulfate fractionation and chromatographical separation on anion exchanger and gel filtration resins. The purified sheep liver MDH specific activity is 6.7 units/mg protein representing 11.6 purification folds and 27.7% yield. The molecular mass of SLMDH intact protein is 68 ± 1.6 kDa. SLMDH turned out to be homogeneous and consists of two identical subunits of 34 ± 1.2 kDa each. The SLMDH isoelectric point (pI) value is estimated at pH 6.2 and displayed its optimum activity at pH 9.6 and has Km value of 1.4 mM for NAD and 11 mM for malate. FeCl2, NiCl2 and ZnCl2 inhibited the SLMDH activity. The purified SLMDH is applied in the preparation of AST diagnostic kit that found sensitive and comparable with a commercially available one.
Keywords: Malate dehydrogenase, Purification,Characterization,Sheep liver, AST diagnostickit.